Updates in Percutaneous Lung Biopsy: New Indications, Techniques and Controversies - Lorenz, Jonathan M. (Seminars in Interventional Radiology, 2012)
The objective of percutaneous chest biopsy is to consistently reach the amount of tissue required to meet or exceed published diagnostic accuracy rates. Many recent publications have reevaluated the subject of chest biopsy to assess borderline or controversial indications such as very small lesions, ground-glass opacities, and cases with a past nondiagnostic percutaneous biopsy. In addition, publications have reviewed sample adequacy for the accurate determination of molecular markers. These new indications promise to expand the numbers of biopsy procedures performed by radiologists. This article discusses the current role of image-guided percutaneous lung biopsies in the management of patients with pulmonary malignancies.
Keywords: interventional radiology; percutaneous biopsy; lung malignancy; molecular markers